TradeU: bridging theory and the market with real-time financial learning - Mohd Azahari, Mas Azra Zakirah; Mohd Nor Azman, Najwa Nadhirah; Amir, Nuramera; Azuan, Nur Madihah; Kamis, Rohaiza (2025)
In Malaysia, finance education remains largely theoretical, leaving students underprepared for realworld trading and market dynamics. To address this gap, TradeU is introduced as an interactive, classroom-based platform integrated with Bursa Malaysia’s tools and localized financial content. The platform enables educators to build digital classrooms where students learn trading fundamentals, analyze live market data, conduct technical analysis, and monitor real-time company news. Its novelty lies in a gamified Bursa Malaysia trading simulation with a leaderboard, promoting engagement through competition and practice. TradeU also supports assignment submission and performance tracking, creating a comprehensive teaching and learning ecosystem. Although financial literacy in Malaysia increased slightly from 60.2% to 62.9% in 2024, overall levels remain stagnant, highlighting the need for impactful solutions. Tailored for university students and finance educators, TradeU fosters investment literacy, analytical thinking, and confidence, demonstrating strong commercialization potential in academia, literacy programs, and professional development.